Ubiquitination and Proteasomal Regulation of Pannexin 1 and Pannexin 3 - Blinder, Anna (Université d'Ottawa / University of Ottawa, 2020)
Pannexin 1 (PANX1) and Pannexin 3 (PANX3) are single-membrane channel glycoproteins that allow for communication between the cell and its environment to regulate cellular differentiation, proliferation, and apoptosis. Their expression is regulated through post-translational modifications, however, their regulation by ubiquitination and the ubiquitin proteasome pathway (UPP) has not been examined. Here, I show that PANX1 is monoubiquitinated and K48- and K63-polyubiquitinated, and PANX3 is polyubiquitinated. While treatment with MG132 altered the banding profile and subcellular distribution of both pannexins, data suggested that only PANX3 is degraded by the UPP. To study the purpose of PANX1 ubiquitination, a PANX1 mutant bearing nine lysine mutations was engineered. Results revealed increased cell surface expression of the mutant, suggesting that ubiquitination may regulate trafficking. I thus demonstrated for the first time that PANX1 and PANX3 are polyubiquitinated and differentially regulated by ubiquitin and by the proteasome, indicating distinct mechanisms that stringently regulate pannexin expression.
Keywords: Pannexin; Ubiquitination; Proteasome; Degradation